2014
DOI: 10.3109/19401736.2013.879649
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and genetic structure of Tunisians and their position within Mediterranean populations

Abstract: Tunisia is located at the crossroads of Europe, the Middle East and Sub-Saharan Africa. This position might lead to numerous waves of migrations, contributing to the current genetic landscape of Tunisians. In this study, we analyzed 815 mitochondrial DNA (mtDNA) sequences from Tunisia in order to characterize the mitochondrial DNA genetic structure of this region, to construct the processes for its composition and to compare it to other Mediterranean populations. To that end, additional 4206 mtDNA sequences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
5
23
0
Order By: Relevance
“…2 ). This is in agreement with previous studies that examined uniparental and autosomal markers and showed a multi-ethnic origin of North Africans [ 27 , 37 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…2 ). This is in agreement with previous studies that examined uniparental and autosomal markers and showed a multi-ethnic origin of North Africans [ 27 , 37 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…The obtained results were discussed in the light of the relatively recent historical relationships between Tunisian and the abovementioned populations [ 27 , 53 , 54 ], in the attempt to clarify the routes followed by LP diffusion and to explore the potential processes of convergent evolution of LP in European and in some non-European populations, such as the Tunisian one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was marked by the invasion of Bedouin tribes (Banu Hilal), followed by the Arabization and Islamization of many Berber populations. Even so, previous studies on Tunisian populations displayed the mosaic structure of the mitochondrial gene pool, which is characterized by an overall high frequency of Eurasian haplogroups (∼70%), followed by Sub‐Saharan L lineages (∼ 25%), and lesser frequencies of North African haplogroups U6 and M1 (5%) (Fadhlaoui‐Zid et al, ; Frigi et al, ; Kefi et al, ). However, of these mtDNA, only Fernandes et al () estimated the recent contribution of Near Eastern sublineages, i.e., K1a1, N1, T, J, R0a, U, and X, suggesting that they arrived around 2000 years ago, probably associated with Phoenician occupation.…”
Section: Introductionmentioning
confidence: 96%